Neural Activity Is Dynamically Modulated by Memory Load During the Maintenance of Spatial Objects - Pan, Yali; Tan, Zheng; Gao, Zhiyao; Li, Yanyan; Wang, Liang (Frontiers in Psychology, 2018)
Visuospatial working memory is a fundamental but severely limited ability to temporarily remember selected stimuli. Several studies have investigated the underlying neural mechanisms of maintaining various visuospatial stimuli simultaneously (i.e., working memory load, the number of representations that maintained in working memory). However, two confounding factors, namely verbal representation and encoding load (the number of items that encoded into working memory), have not been well controlled in previous studies. In this study, we developed a novel delayed-match-to-sample task (DMST) controlling for these two confounding factors and recorded scalp EEG signals during the task. We found that behavioral performance deteriorated severely as memory load increased. Neural activity was modulated by working memory load in a dynamic manner. Specifically, higher memory load induced stronger amplitude in occipital and central channel-clusters during the early delay period, while the inverse trend was observed in central and frontal channel-clusters during late delay. In addition, the same inverse memory load effect, that was lower memory load induced stronger amplitude, was observed in occipital channel-cluster alpha power during late delay. Finally, significant correlations between neural activity and individual reaction time showed a role of late-delay central and frontal channel-cluster amplitude in predicting behavioral performance. Because the occipital cortex is important for visual information maintenance, the decrease in alpha oscillation was consistent with the cognitive role that is ‘gating by inhibition’. Together, our results from a well-controlled DMST suggest that working memory load not exerted constant but dynamic effect on neural activity during maintenance of visuospatial objects.